Analisis Wacana Kritis Michel Foucault terhadap Representasi Kasus Bullying Timothy Anugrah Saputra dalam Podcast Denny Sumargo - Jelita Christy Sianipar; Enjelika Barus; Neni Lasinta Lumban Siantar; Indah Lestari Hasugian; Sarma Panggabean (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This study aims to analyze the construction of discourse, power relations, and the production of truth in a podcast discussing Timothy's case using Michel Foucault's Critical Discourse Analysis framework. The focus of the research lies in how power works through language, body, institutions, and discursive practices in shaping subjects and producing "truth" about the tragedy in the public sphere. The research data consists of the entire discourse in the podcast, starting from minute 00:00 until the end. All data are analyzed through Foucauldian categories, namely the regime of truth, power/knowledge, medical gaze, disciplinary power, biopower, governmentality, subjectivation, politics of silence, and counter-discourse. The results show that the discourse in the podcast not only constructs an informative narrative but also produces power relations that influence how society understands the tragedy. Medical and psychological discourses position Timothy as a pathological subject, while family discourse forms a counter-discourse to reclaim his identity. The media acts as an institution that determines the framework of interpretation, while the state through the Ministry and the police emerges as the official producer of truth. Furthermore, the interaction between religious power, educational power, and social power demonstrates that truth is not an objective entity, but rather a dynamic construction produced through inter-discursive struggles. This research confirms that Foucault's analysis effectively uncovers invisible power structures in contemporary social events.